The Use of MBO (Management of Objectives) Method of Attraction and Evaluation of Effectiveness of Investments to the Tourism and Hospitality - Vinogradova, Marina V.; KulyaminÐ°, Ðžlga S.; Larionova, Anna A.; Maloletko, Alexandr N.; Kaurova, Olga V. (International Review of Management and Marketing, 2016)
The article aims to elaborating of proposals for improvement of the mechanism of investments attraction to tourism and hospitality, based on the use of MBO approach. In the course of the present work the methods of modeling, expert assessments, economic-mathematical measurement, extrapolation, scenario approach, factor and comprehensive analysis have been applied. They allow considering the posed problem as a focused and structured process of improvement of the mechanisms of attraction and evaluation of the effectiveness of investments to the tourism and hospitality, taking into account the use of programs at various levels and industry characteristics. The article reveals the drawbacks of the mechanisms of investment programs implementation for the tourism and hospitality sphere, such as: the lack of effective investment infrastructure, ensuring the free exchange of information among entrepreneurial entities; nonexistence of reliable support tools of effective investment management. The article represents a model of making investment decisions in the tourism and hospitality sphere, including the priority relation of intensity of achievement the set objectives, the behavior of the target functions during the implementation of alternative solutions and the results of evaluation of the state and conduct of the environment. It also discloses the mechanism of evaluation of investments effectiveness, covering not only the stage of designing, construction, putting into operation, but also the extension of date of the investment period on post-paid-off term. Keywords: Investments, MBO (Management by Objective), Investment Effectiveness, Tourism and Hospitality JEL Classifications: O15, P21, Z32